The usage of prior upper gastrointestinal endoscopy among symptomatic patients undergoing cholecystectomy - Khan, Ayesha Jule; Gupta, Samridhi; Kohli, Manu; Bhargava, Gopal S. (International Surgery Journal, 2020)
Background: Cholelithiasis is one of the most common problems encountered in surgery. It is an immense challenge to discriminate between signs and symptoms due to gastrointestinal lesions and gallstones diseases. The objective of this study was to evaluate the usage of pre-operative upper gastrointestinal endoscopy (UGE) as a routine in treating symptomatic gallstone patients. Methods: This prospective hospital based observational study was conducted in the Department of General Surgery at Sri Guru Ram Das Institute of Medical Sciences and Research, Sri Amritsar from January 2018 to June 2019. 60 symptomatic gallstone patients were selected for cholecystectomy and preoperative upper gastrointestinal (GI) endoscopy evaluation was done for any associated upper gastrointestinal problems. Results: Out of the total patients, females constituted 85% of overall study patients and majority of the patients presented with atypical biliary colic symptoms (55%, group 2) whereas 45% presented with typical biliary colic symptoms (group 1) (p value=0.009). Relief rate was highest in group 1 with abnormal UGE than with group 2. Conclusions: The routine use of upper GI endoscopy in patients with symptomatic cholelithiasis prior to cholecystectomy will help reduce post-operative persistence of symptoms and thus, it is a useful investigation in the overall treatment of gallstone diseases.